Papel relativo de dispersores biológicos na montagem de comunidades de protistas ciliados. - Cochak, Crislaine (2019)
Vertebrates and invertebrates are known as important biological vectors in the dispersal of terrestrial neotropical communities (e.g. plants, animals). However, its role in the formation and maintenance of the microbial community in aquatic ecosystems is, in general, greatly underestimated. The objective was to evaluate the relative role of different biological vectors (amphibians and odonates) in the dispersion and consequent structuring of ciliate protozoan communities. An experiment was carried out in the open air, simulated in polyethylene pots, for 33 days, 4 treatments were designated a control with only the action of the wind, without addition of propagules one with addition of propagules from odonatas washes, one with addition of propagules from amphibian washes and one with addition of propagules from washes of both vectors. There were 54 species of ciliates, distributed in 9 orders, being the most representative Hymenostomatida and Peritrichia. The results showed that animal vectors represent an important pathway for the dispersion of ciliates. The species richness and abundance of ciliates showed a significant increase in their values, markedly after the 12th day of experiment. For the species composition, differences were evidenced between the treatments, within each time, as well as between the different treatments throughout the experiment. The dynamics of the dispersion of ciliary protists was enhanced when mediated by biological vectors, especially amphibians. Emphasizing that the nature of the propagule (forms of resistance or active) seems to play a relevant role in the dispersion and colonization capacity, determining the structure and dynamics of the ciliate protist communities.